Protection of Young Artist Style Paintings from the Perspective of Copyright and Traditional Cultural Expression in the Digital Era - NARESWARI, Ni Nyoman Claudia; Dharmawan, Ni Ketut Supasti (Protection: Journal Of Land And Environmental Law, 2026)
The purpose of this study is to analyze the legal protection of Young Artist-style paintings from the perspective of copyright and traditional cultural expressions amidst the development of the digital era. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a comparative approach. The results of the study indicate that legally, Young Artist-style paintings are included in the category of creations in the field of fine arts, as regulated in Law Number 28 of 2014 concerning Copyright. However, because the work is sourced from communal Balinese cultural values, individual protection through copyright is not entirely adequate. Therefore, legal recognition is needed, namely through Traditional Cultural Expressions (EBT), to protect the moral rights and cultural identity of the Sayan Village community. In the digital context, the biggest challenge lies in the possibility of being produced/recreated by artificial intelligence along with the development of the current digital era. Effective protection efforts can be carried out through strengthening national regulations, establishing a digital cultural expression database, and implementing technologies such as Digital Rights Management (DRM) or blockchain certificates to guarantee the attribution and authenticity of works. This research confirms that protecting Young Artist style paintings is not only a legal obligation, but also a form of responsibility